2019
DOI: 10.33423/jmdc.v13i3.2241
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Presence at Work: A Practice – Oriented Framework

Abstract: Leadership or executive presence can be a nebulous concept, making it difficult for leaders to understand and put into practice. When behaviorally defined and operationalized, presence can strengthen a leader's personal brand equity, career competitiveness and organizational impact. After a brief review of some relevant literature, a four-phase practice-oriented framework is offered. This dynamic process helps a leader more fully understand and use leadership presence at work, including managing the relevant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Organizationally, leadership presence influences healthier work environments and cultivated positive work cultures. [3][4][5]10,13,15,17,19,21,[23][24][25][26][27][28] Ahmad and Loch 3 identified that team success contributed to cooperative outcomes, with Bleich 15 discovering similar elements, but added an additional element of goal achievement. Similarly, Chrobot et al 17 recognized that leadership presence fostered alignment through shared goals and achievement.…”
Section: Organizational Consequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Organizationally, leadership presence influences healthier work environments and cultivated positive work cultures. [3][4][5]10,13,15,17,19,21,[23][24][25][26][27][28] Ahmad and Loch 3 identified that team success contributed to cooperative outcomes, with Bleich 15 discovering similar elements, but added an additional element of goal achievement. Similarly, Chrobot et al 17 recognized that leadership presence fostered alignment through shared goals and achievement.…”
Section: Organizational Consequencesmentioning
confidence: 99%
“…Similarly, because leaders served as role models, Kerns found that emulating this practice contributed to optimal patient outcomes. 13 Tahan 5…”
Section: Organizational Consequencesmentioning
confidence: 99%
See 2 more Smart Citations